Mineralogical characterization of calcification in cardiovascular aortic atherosclerotic plaque: A case study. (August 2014) - Li, Yan; Wang, Xin; Zhu, Meiqian; Yang, Chong-Qing; Lu, Anhuai; Li, Kang; Meng, Fanlu; Wang, Changqiu
Abstract: Calcification in cardiovascular aortic atherosclerotic plaque contains Ca-phosphate minerals. However, most research on cardiovascular calcification has focused on its physiological properties rather than its mineralogical features. In this present study, cardiovascular calcification was characterized by collecting samples from patients' tissues and applying mineralogical techniques. Synchrotron radiation-based micro-X-ray diffraction showed the calcification had a similar structure to hydroxylapatite (HAp). Transmission electron microscopy showed some structurally HAp-like spherical particles with a diameter of ∼200 nm and acicular crystals ∼100 nm × ∼20 nm in size. Selected-area electron diffraction indicated that these mineral particles belonged to the hexagonal crystal system. Fourier-transform infrared (FTIR) spectroscopy showed three typical peaks at 1469 cm −1, 1455 cm −1 and 1413 cm −1, indicating that the carbonate group in the calcification plaque substituted for a hydroxyl group to form B-type CHAp (Ca10 (PO4, CO3 ) x (OH) y ). The FTIR mapping results illustrated the intergrowth of calcification and organic tissues and the inhomogeneous substitution of phosphate by carbonate in the calcification area. X-ray absorption near-edge structure analysis affirmed that the chemical environments of Ca in the calcification were close to those in HAp. Based on these mineralogical characteristics, the calcification in plaque is identified as a mixture phase of HAp and B-type carbonate HAp, which is similar to the composition of bones.